The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00401-018-1895-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proteome solubility indicate widespread proteostatic disruption in mouse models of neurodegenerative disease

Abstract: The deposition of pathologic misfolded proteins in neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, frontotemporal dementia and amyotrophic lateral sclerosis is hypothesized to burden protein homeostatic (proteostatic) machinery, potentially leading to insufficient capacity to maintain the proteome. This hypothesis has been supported by previous work in our laboratory, as evidenced by the perturbation of cytosolic protein solubility in response to amyloid plaques in a mouse model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 105 publications
6
28
0
Order By: Relevance
“…3, 4). As expected based on our previous results [34], synthesis of many proteins was suppressed by tau expression; however, we also identified many proteins that were increased as a consequence of tau expression, which corroborates results that were recently described [41]. Strikingly, transcript levels coding for ribosomal genes were unchanged while the protein levels were rescued by tau suppression, supporting the hypothesis that a shift in translation occurs during the window where doxycycline treatment rescues cognitive impairment in these mice.…”
Section: Discussionsupporting
confidence: 93%
“…3, 4). As expected based on our previous results [34], synthesis of many proteins was suppressed by tau expression; however, we also identified many proteins that were increased as a consequence of tau expression, which corroborates results that were recently described [41]. Strikingly, transcript levels coding for ribosomal genes were unchanged while the protein levels were rescued by tau suppression, supporting the hypothesis that a shift in translation occurs during the window where doxycycline treatment rescues cognitive impairment in these mice.…”
Section: Discussionsupporting
confidence: 93%
“…Instead, there is a wider metastable subproteome that underlies specific pathological responses to different stresses. These findings complement those of a recent large-scale proteomic study that identified a small number of endogenous proteins that are prone to aggregation in mouse models of different neurodegenerative diseases, including AD, PD and ALS, indicating the presence of metastable subproteome (80). We also note that our results are compatible with the possibility that aggregation occurs more non-specifically if protein folding is generally perturbed.…”
Section: Discussionsupporting
confidence: 90%
“…The pellets were suspended in Laemmeli buffer [21] and stored as the SDS-P fractions. As in previous work using LC-MS/MS, the primary comparison was between PBS soluble fractions (PBS-S) and SDS insoluble fractions (SDS-P) to identify proteins that are normally readily detectable in soluble fractions but became over-represented in insoluble fractions in mice with Aβ pathology [34,42].…”
Section: Protein Identification By Lc-ms/msmentioning
confidence: 99%
“…In prior studies of the APPswe/PS1dE9 model of Alzheimer-type amyloidosis, we observed age-dependent changes in the solubility of the proteome such that cytosolic brain proteins became over-represented in SDSinsoluble extracts [34,42]. A subset of the proteins identified in the APPswe/PS1dE9 model were also identified as losing solubility in mice that model neurofibrillary tangle (NFT) pathology, superoxide dismutase 1 (SOD1) pathology, and α-synuclein pathology [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation